2023
DOI: 10.1109/access.2023.3249967
|View full text |Cite
|
Sign up to set email alerts
|

U-Shaped Low-Complexity Type-2 Fuzzy LSTM Neural Network for Speech Enhancement

Abstract: Speech enhancement (SE) aims to improve the intelligibility and perceptual quality of speech contaminated by noise signals through spectral or temporal changes. Deep learning models achieve speech enhancement and estimate the magnitude spectrum. This paper proposes a novel and computationally efficient deep learning model to enhance noisy speech. The model pre-processes the noisy speech magnitude by redistributing energy from high-energy voiced segments to low-energy unvoiced segments using an adaptive power l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Phase plays a vital role in improving the perceptual speech quality where a complex Phase spectrum can add significant quality and intelligibility improvements in speech enhancement system [ 49 51 ]. The focus of this study is to estimate speech magnitude enhancement where the noisy phase is used during speech waveform reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Phase plays a vital role in improving the perceptual speech quality where a complex Phase spectrum can add significant quality and intelligibility improvements in speech enhancement system [ 49 51 ]. The focus of this study is to estimate speech magnitude enhancement where the noisy phase is used during speech waveform reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…These models can be used to perform classic DSP tasks such as noise reduction, pitch and formant manipulation, and prosody modification [75]. Saleem et al [76] suggested a computationally efficient deep learning model for improving noisy voice. For magnitude estimation, their model used a U-shaped fuzzy long short-term memory, which outperformed other deep learning models and significantly enhanced speech intelligibility and quality.…”
Section: Algorithms For Alaryngeal Speech Enhancementmentioning
confidence: 99%